Analyzing the Use and extensions of UTAUT Model - Rito, P. N. (2012)
In the investigation that is being developed, one of the important aspects is to know and adopt/ nominate/choose one of the existing models that explains the adoption and use by individuals of a new technology, in an organization. Of the various models that exists in the literature, UTAUT is our choice. From the literature review that has taken place so far, on the implementation of the UTAUT model, we have particular interest on the results obtained in cases of complex technologies adoption and of voluntary use. The use of models such as the UTAUT also serve as tools that enable information systems professionals to forecast the adoption / resistance before it takes shape and to advance interventions in order to streamline the impact on individuals adopters.